Sweetness Taste Preference Levels and Their Relationship to the Nutritional and Dental Caries Patterns among Brazilian Preschool Children - Souza Porcelli, Ilma Carla de; Corsi, Nathalia Maciel; Esteves Barata, Terezinha de Jesus; Calvo Fracasso, Marina de Lourdes; Poli-Frederico, Regina Celia; Seixas, Gabriela Fleury; Andrade, Flaviana Bombarda de [UNESP]; Maciel, Sandra Mara (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2019)
Objective: To evaluate the sweetness taste preference levels and their relationship with the nutritional and dental caries patterns among preschool children. Material and Methods: The participants of this cross-sectional study were 191 children aged 4 to 5 years, who were regularly attending public Child Education Centers of a city southern Brazil. Children's preference for sugar was evaluated by the Sweet Preference Inventory; caries prevalence, according to the World Health Organization criteria, and nutritional status, by anthropometric weight and stature measurements, in accordance with child growth standards of the World Health Organization. Results: High levels of sweetness preference were identified. The majority of children (67.5%) opted for the most concentrated sucrose solutions. Excess weight was recorded in 27.7% of the preschoolers. The prevalence of caries was 51.8%, with the mean dmf-t equal to 1.92 (+/- 2.72) and the decayed (c) component responsible for 94.2% of the index. No significant association between sweetness preference and the nutritional or the oral health patterns could be established. In addition, no association between excess weight and dental caries was identified. The diseases studied were only associated with sociodemographic variables. Excess weight was associated with maternal age (p=0.001) and caries experience with family income (p=0.013). Conclusion: No significant associations could be stablished between the sweetness taste preference and the diseases studied, nor between excess weight and dental caries. However, the findings of high patterns of sweet preference, excess weight and untreated caries experience, highlight the need for the implementation of integrated public policies aimed at controlling both nutritional and of oral health problems in the studied population.
Keywords: Oral Health; Dental Caries; Nutritional Status; Taste Perception